Unambiguous determination of farnesol and tyrosol in vaginal fluid using fast and sensitive UHPLC-MS/MS method - Pilařová, Veronika; Kočová Vlčková, Hana; Jung, Ondřej; Protti, Michele; Buchta, Vladimír; Mercolini, Laura; Svec, Frantisek; Nováková, Lucie (Analytical and bioanalytical chemistry, 2020)
The new ultra-high performance liquid chromatography method with tandem mass spectrometry detection (UHPLC-MS/MS) has been optimized to allow fast, selective, and high-throughput analysis of two Candida albicans quorum sensing molecules (QSM), farnesol and tyrosol. The problem of the presence of the interference in the samples and system was successfully solved by careful optimization of chromatographic conditions. Charged hybrid stationary phase modified with pentafluorophenyl group and optimized gradient elution provided adequate separation selectivity and peak shapes. The impurity was identified as dibutyl phthalate and had the same m/z ions as farnesol leading to an important interference on selected reaction monitoring channel. Two different types of biological matrices originating from vaginal fluid, supernatant and sediment, were analysed. Micro-solid phase extraction in pipette tips was optimized for the selective isolation of QSM from the supernatant. The insufficient retention of farnesol on the extraction sorbent was improved when 1% of organic solvent was added prior to extraction, while the retention of tyrosol was only possible when using combined C8 and polymer sorbent type. Strong retention of farnesol had to be solved by increasing elution solvent strength and volume up to 600 μL. However, this approach did not allow the pretreatment of sediment samples due to the sorbent clogging. Therefore, our previously developed protein precipitation method was modified and validated to analyse the sediments. New developed UHPLC-MS/MS method provided suitable accuracy and precision for the determination of QSM in vaginal fluid while using only 50 μL sample volume and two different sample preparation methods.
Keywords: vagina; Candida albicans; Middle Aged; Limit of Detection; limita detekce; Chromatography, High Pressure Liquid; Adult; mladý dospělý; vysokoúčinná kapalinová chromatografie; Tyrosol; Young Adult; ženské pohlaví; Humans; Tandem Mass Spectrometry; fenethylalkohol; Quorum sensing; farnesol; lidé středního věku; Phenylethyl Alcohol; Vagina; tandemová hmotnostní spektrometrie; UHPLC-MS/MS; dospělí; Microextraction; Female; Farnesol; lidé